Globalization a very short introduction - Steger, Manfred B. (1961- ...). (Oxford ; New York : Oxford University Press, 2003)
"Manfred B. Steger presents globalization in accessible language as a multifaceted process encompassing global, regional, and local aspects of social life. He explores whether it is a new phenomenon, and if it should be considered a 'good' or 'bad' thing - a question that has been hotly debated in classrooms, boardrooms, and on the streets - especially since the 9/11terrorist attacks."--Resume de l'editeur.
Notes bibliogr. Index.
Keywords: Globalization; Mondialisation; globalism; Globalization; Mondialisation; globalisation (mondialisation); globalisation (mondialisation)